Functional analysis of a novel nonsense variant c.91A>T of the TRAPPC2 gene in a Chinese family with X-linked recessive autosomal spondyloepiphyseal dysplasia tarda - Lou, Guiyu; Zhao, Yuanyin; Zhao, Huiru; Zhang, Yuwei; Hao, Bingtao; Qin, Litao; Liu, Hongyan; Liao, Shixiu (Frontiers in Genetics, 2023)
Spondyloepiphyseal dysplasia tarda (SEDT) is a late-onset X-linked recessive skeletal dysplasia caused by mutations in the TRAPPC2 gene. In this paper, we identified a novel nonsense variant in a SEDT pedigree and analyzed the function of the variant in an attempt to explain the new pathogenesis of the TRAPPC2 protein in SEDT. In brief, DNA and RNA samples from the peripheral blood of SEDT individuals were prepared. The causative variant of the Chinese SEDT family was identified by clinic whole exome sequencing analysis. Then, we observed mRNA expression of TRAPPC2 in patients and the mutant TRAPPC2 level in vitro and analyzed the protein stability and subcellular distribution by Cell fluorescence and western blotting. We also investigated the effect of TRAPPC2 knockdown on the expression and secretion of COL2A1 in SW1353 cells or primary human chondrocytes. Herein, we found a nonsense variant, c.91A>T of the TRAPPC2 gene in the pedigree. TRAPPC2 mRNA expression levels were significantly decreased in available peripheral blood cell samples of two affected patients. In vitro study displayed that the mutant plasmid exhibited significantly lower mRNA and protein of TRAPPC2 and the mutant protein changed its membrane distribution. Knockdown TRAPPC2 resulted in decreased COL2A1 expression and collagen II secretions. Our data indicate that the novel nonsense variant, c.91A>T of the TRAPPC2 gene is the cause of SEDT in this pedigree. The variant results in a down expression of TRAPPC2, then effect the COL2A1 expression and collagen II secretions, which may explain the mechanism of loss of function of the variant.